Pseudoxanthoma elasticum-like papillary dermal elastolysis - Bagher Zadeh, Valid (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
Elastolysis refers to a loss of elastic fibers. It can affect the papillary dermis, the reticular dermis, or both. Pseudoxanthoma elasticum-like papillarydermal elastolysis (PXE-PDE) is a clinicopathological entity first described by Rongioletti and Rebora in 1992 (1). It is an acquired elastolyticdisorder that mainly affects the papillary dermis. Clinically it resembles pseudoxanthoma elasticum (PXE), but it differs histologically and there is no systemic involvement, in contrast to PXE.
Keywords: elastičnost; koža; kožne bolezni; starostniki